1999
DOI: 10.1042/0264-6021:3380107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of proprotein convertases-1, -7 and furin by diterpines of Andrographis paniculata and their succinoyl esters

Abstract: Studies were performed to investigate the prohormone/proprotein convertase (PC)-inhibitory properties of chemical constituents of the medicinally active plant Andrographis paniculata (AP; from the family Acanthaceae), also known as 'King of Bitters'. Among the individual components tested against the clinically important convertases, furin and PC1, neoandrographolide (a C3 O-glucoside derivative of the major constituent andrographolide) exhibited the highest inhibitory action with an IC50 of 53.5 microM agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…These compounds have the potential to be developed as antitumor agents. These results are supported by a different finding, where it was demonstrated that the succinoyl ester of andrographolide significantly inhibited proprotein convertases and thus displayed potent antiviral activities against HIV-1 and HIV-2 [89]. These results emphasize that some of the derivatives of andrographolide might be much more potent that the parent compound itself and call for a dedicated line of investigations to prove their potential.…”
Section: Introductionsupporting
confidence: 57%
“…These compounds have the potential to be developed as antitumor agents. These results are supported by a different finding, where it was demonstrated that the succinoyl ester of andrographolide significantly inhibited proprotein convertases and thus displayed potent antiviral activities against HIV-1 and HIV-2 [89]. These results emphasize that some of the derivatives of andrographolide might be much more potent that the parent compound itself and call for a dedicated line of investigations to prove their potential.…”
Section: Introductionsupporting
confidence: 57%
“…Some groups have previously investigated the inhibitory effects of some molecules that could be used as lead compounds for the molecular scaffolds that are required for further inhibitor development. A number of natural compounds derived from plants called andrographolides have shown weak potency inhibition (low micromolar inhibition) against furin, PC1/3 and PC7 (105). All of the effective constituents of the plant Andrographis paniculata have a diterpine labdane skeleton in common, shown in Table 2, that could be exploited to generate inhibitors as good as peptide-based compounds.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…In addition, andrographolide belongs to the diterpene lactones, and has been reported to have multiple pharmacologic properties, such as protozoacidal activity, inhibition of platelet aggregation, inhibition of protein convertases-1 and -7, and furin, stimulation of cell differentiation, and anti-hepatotoxic activity, and may be developed as the drug for treatment of tissue injury, septic shock, and autoimmune diseases [110115]. We found that puerarin [9092] and andrographolide [9395] also posses the ability to activate α 1 -ARs, especially the α 1A -subtype, to enhance β -endorphin secretion from adrenal glands of STZ-diabetic rats (Table 1, Figure 1).…”
Section: Mediation Of Endogenous β-Endorphin In the Plasma Glucosementioning
confidence: 99%